To stop or not to stop: what should we be doing with biologic DMARDs when patients undergo orthopaedic surgery? - van Duren, BH; Wignall, A; Rangan, A; Coates, L; Pandit, H; Mankia, K (Oxford University Press, 2021)
Management of biologic DMARDs in patients undergoing orthopaedic surgery is variable; flare avoidance is a priority.